Assimilating Atmosphere Reanalysis in Coupled Data Assimilation - 刘华然 卢飞雨 刘征宇 刘赟 张绍晴 (Acta meteorologica Sinica, 2016)
This paper tests the idea of substituting the atmospheric observations with atmospheric reanalysis when setting up a coupled data assimilation system.The paper focuses on the quantification of the effects on the oceanic analysis resulted from this substitution and designs four different assimilation schemes for such a substitution.A coupled Lorenz96 system is constructed and an ensemble Kalman filter is adopted.The atmospheric reanalysis and oceanic observations are assimilated into the system and the analysis quality is compared to a benchmark experiment where both atmospheric and oceanic observations are assimilated.Four schemes are designed for assimilating the reanalysis and they differ in the generation of the perturbed observation ensemble and the representation of the error covariance matrix.The results show that when the reanalysis is assimilated directly as independent observations,the root-mean-square error increase of oceanic analysis relative to the benchmark is less than 16%in the perfect model framework;in the biased model case,the increase is less than 22%.This result is robust with sufficient ensemble size and reasonable atmospheric observation quality（e.g.,frequency,noisiness,and density）.If the observation is overly noisy,infrequent,sparse,or the ensemble size is insufficiently small,the analysis deterioration caused by the substitution is less severe since the analysis quality of the benchmark also deteriorates significantly due to worse observations and undersampling.The results from different assimilation schemes highlight the importance of two factors：accurate representation of the error covariance of the reanalysis and the temporal coherence along each ensemble member,which are crucial for the analysis quality of the substitution experiment.